Simplify by combining like terms:
4x² - 5x² + 8x - 11x + 6 + 2
-x² - 3x + 8
The simplified form is -x² - 3x + 8.
4x²+8x-11x+6-5x²+2
39 answers
What are the coefficients in the polynomial 4x²+3x-3
4, -3, -3
4,3
4,3,3
-4,-3
4, -3, -3
4,3
4,3,3
-4,-3
4, 3, -3
(M²-m-3)+(m-4)
Simplify by combining like terms:
M² - m - 3 + m - 4
M² - 7
The simplified form is M² - 7.
M² - m - 3 + m - 4
M² - 7
The simplified form is M² - 7.
(5x²+x-3)-(-2x³+4)
Distribute the negative sign:
5x² + x - 3 + 2x³ - 4
Collect like terms:
2x³ + 5x² + x - 7
The simplified form is 2x³ + 5x² + x - 7.
5x² + x - 3 + 2x³ - 4
Collect like terms:
2x³ + 5x² + x - 7
The simplified form is 2x³ + 5x² + x - 7.
Suppose you earn 8t - 3 dollars on Monday and 6t+5 dollars on Tuesday what were your total earnings? Simplify your answer
To find the total earnings, we need to add the earnings from Monday and Tuesday:
Total earnings = (8t - 3) + (6t + 5)
Simplify by combining like terms:
Total earnings = 8t + 6t - 3 + 5
Total earnings = 14t + 2
The simplified form is 14t + 2 dollars.
Total earnings = (8t - 3) + (6t + 5)
Simplify by combining like terms:
Total earnings = 8t + 6t - 3 + 5
Total earnings = 14t + 2
The simplified form is 14t + 2 dollars.
F⁷×f¹
When multiplying exponential expressions with the same base, you add the exponents.
So, F⁷ × f¹ = F^(7+1) = F⁸
The simplified form is F⁸.
So, F⁷ × f¹ = F^(7+1) = F⁸
The simplified form is F⁸.
144¹⁴/144²
When dividing exponential expressions with the same base, you subtract the exponents.
So,
144¹⁴ / 144² = 144^(14-2) = 144¹²
The simplified form is 144¹².
So,
144¹⁴ / 144² = 144^(14-2) = 144¹²
The simplified form is 144¹².
X¹⁶/x³
When dividing exponential expressions with the same base, you subtract the exponents.
So,
x¹⁶ / x³ = x^(16-3) = x¹³
The simplified form is x¹³.
So,
x¹⁶ / x³ = x^(16-3) = x¹³
The simplified form is x¹³.
Which of the following expressions is true
4³×4⁴=4¹²
5²x5³>5⁵
3²x3⁵=¹⁰
5²x5⁴<5⁸
4³×4⁴=4¹²
5²x5³>5⁵
3²x3⁵=¹⁰
5²x5⁴<5⁸
4³×4⁴=4¹² is true, because when you multiply exponential expressions with the same base, you add the exponents. So, 4³×4⁴ = 4^(3+4) = 4⁷, which is equal to 4¹².
5²x5³>5⁵ is also true, because 5²x5³ = 5^(2+3) = 5⁵, which is equal to 5⁵.
3²x3⁵=¹⁰ is false, because 3²x3⁵ = 3^(2+5) = 3⁷, which is not equal to 10.
5²x5⁴<5⁸ is true, because 5²x5⁴ = 5^(2+4) = 5⁶, which is less than 5⁸.
5²x5³>5⁵ is also true, because 5²x5³ = 5^(2+3) = 5⁵, which is equal to 5⁵.
3²x3⁵=¹⁰ is false, because 3²x3⁵ = 3^(2+5) = 3⁷, which is not equal to 10.
5²x5⁴<5⁸ is true, because 5²x5⁴ = 5^(2+4) = 5⁶, which is less than 5⁸.
Which of the following Expressions is true
2⁴x2⁴>2⁷
3²x3⁶=3⁷
4³x4⁵<4⁸
5²x5³=5⁶
2⁴x2⁴>2⁷
3²x3⁶=3⁷
4³x4⁵<4⁸
5²x5³=5⁶
2⁴x2⁴>2⁷ is false, because 2⁴x2⁴ = 2^(4+4) = 2⁸, which is greater than 2⁷.
3²x3⁶=3⁷ is also false, because 3²x3⁶ = 3^(2+6) = 3⁸, which is not equal to 3⁷.
4³x4⁵<4⁸ is true, because 4³x4⁵ = 4^(3+5) = 4⁸, which is equal to 4⁸.
5²x5³=5⁶ is true, because 5²x5³ = 5^(2+3) = 5⁵, which is equal to 5⁶.
3²x3⁶=3⁷ is also false, because 3²x3⁶ = 3^(2+6) = 3⁸, which is not equal to 3⁷.
4³x4⁵<4⁸ is true, because 4³x4⁵ = 4^(3+5) = 4⁸, which is equal to 4⁸.
5²x5³=5⁶ is true, because 5²x5³ = 5^(2+3) = 5⁵, which is equal to 5⁶.
2³/2³
When dividing exponential expressions with the same base, you subtract the exponents.
So,
2³ / 2³ = 2^(3-3) = 2⁰
Any number to the power of 0 equals 1.
So, the simplified form is 1.
So,
2³ / 2³ = 2^(3-3) = 2⁰
Any number to the power of 0 equals 1.
So, the simplified form is 1.
3³/3⁶
When dividing exponential expressions with the same base, you subtract the exponents.
So,
3³ / 3⁶ = 3^(3-6) = 3^(-3)
A negative exponent indicates that the base should be in the denominator.
So,
3^-3 = 1/3^3 = 1/27
The simplified form is 1/27.
So,
3³ / 3⁶ = 3^(3-6) = 3^(-3)
A negative exponent indicates that the base should be in the denominator.
So,
3^-3 = 1/3^3 = 1/27
The simplified form is 1/27.
Multiply write the results in scientific notation
(1.4x10¹)(8x10⁴)
(1.4x10¹)(8x10⁴)
To multiply numbers in scientific notation, multiply the coefficients and add the exponents.
So,
(1.4x10¹)(8x10⁴) = (1.4x8)(10¹ x 10⁴) = 11.2 x 10⁵
11.2 is not in scientific notation, so we need to convert it.
11.2 = 1.12 x 10¹
So,
(1.4x10¹)(8x10⁴) = 1.12 x 10¹ x 10⁵ = 1.12 x 10⁶
The answer, in scientific notation, is 1.12 x 10⁶.
So,
(1.4x10¹)(8x10⁴) = (1.4x8)(10¹ x 10⁴) = 11.2 x 10⁵
11.2 is not in scientific notation, so we need to convert it.
11.2 = 1.12 x 10¹
So,
(1.4x10¹)(8x10⁴) = 1.12 x 10¹ x 10⁵ = 1.12 x 10⁶
The answer, in scientific notation, is 1.12 x 10⁶.
Multiply write the results in scientific notation (1.7x10-⁴)(5x10-⁵)
To multiply numbers in scientific notation, multiply the coefficients and add the exponents.
So,
(1.7x10⁻⁴)(5x10⁻⁵) = (1.7x5)(10⁻⁴ x 10⁻⁵) = 8.5 x 10⁻⁹
The answer, in scientific notation, is 8.5 x 10⁻⁹.
So,
(1.7x10⁻⁴)(5x10⁻⁵) = (1.7x5)(10⁻⁴ x 10⁻⁵) = 8.5 x 10⁻⁹
The answer, in scientific notation, is 8.5 x 10⁻⁹.
8t⁵x8t⁵
When multiplying exponential expressions with the same base, you add the exponents.
So,
8t⁵ x 8t⁵ = (8 x 8) t^(5+5) = 64t¹⁰
The simplified form is 64t¹⁰.
So,
8t⁵ x 8t⁵ = (8 x 8) t^(5+5) = 64t¹⁰
The simplified form is 64t¹⁰.
-x(6x-7)
Use the distributive property:
-x(6x-7) = -x(6x) - x(-7)
= -6x² + 7x
The simplified form is -6x² + 7x.
-x(6x-7) = -x(6x) - x(-7)
= -6x² + 7x
The simplified form is -6x² + 7x.
5k²(6k²-2k+6)
Use the distributive property:
5k²(6k²-2k+6) = 5k²(6k²) - 5k²(2k) + 5k²(6)
= 30k⁴ - 10k³ + 30k²
The simplified form is 30k⁴ - 10k³ + 30k².
5k²(6k²-2k+6) = 5k²(6k²) - 5k²(2k) + 5k²(6)
= 30k⁴ - 10k³ + 30k²
The simplified form is 30k⁴ - 10k³ + 30k².
5k²(-6k²-2k+6)
Use the distributive property:
5k²(-6k²-2k+6) = 5k²(-6k²) - 5k²(2k) + 5k²(6)
= -30k⁴ - 10k³ + 30k²
The simplified form is -30k⁴ - 10k³ + 30k².
5k²(-6k²-2k+6) = 5k²(-6k²) - 5k²(2k) + 5k²(6)
= -30k⁴ - 10k³ + 30k²
The simplified form is -30k⁴ - 10k³ + 30k².
(2k+1)(k-4)
Use the distributive property:
(2k+1)(k-4) = 2k(k-4) + 1(k-4)
= 2k² - 8k + k - 4
= 2k² - 7k - 4
The simplified form is 2k² - 7k - 4.
(2k+1)(k-4) = 2k(k-4) + 1(k-4)
= 2k² - 8k + k - 4
= 2k² - 7k - 4
The simplified form is 2k² - 7k - 4.
(-2y+5)(y+3)
Use the distributive property:
(-2y+5)(y+3) = -2y(y+3) + 5(y+3)
= -2y² - 6y + 5y + 15
= -2y² - y + 15
The simplified form is -2y² - y + 15.
(-2y+5)(y+3) = -2y(y+3) + 5(y+3)
= -2y² - 6y + 5y + 15
= -2y² - y + 15
The simplified form is -2y² - y + 15.